Using the CCAFS Mitigation Options Tool to identify mitigation co-benefits in Ethiopia’s land use sector - Feliciano, Diana (2018)
CCAFS, the University of Aberdeen, USDA, ILRI and EIAR invited a wide range of stakeholders interested in climate change adaptation and mitigation to field activities and a worshop that would apply CCAFS-MOT to the Ethiopian context. These activities included field work for data collection and a three-day workshop; the workshop was composed of one day to train the trainers, one day to train technicians, and a one-day seminar for policy makers and policy advisors. The workshop took place at the ILRI (International Livestock Research Institute) campus in Addis Ababa, Ethiopia on the 23rd, 26-27th March 2018. Participants included representatives from Ethiopian ministries, universities, research institutes, NGOs, students. Please find the invitation letter in Appendix 1, the full participant list in Appendix 2 and the workshop agenda in Appendix 3.